Чисельная гидродинамическая модель атмосферной дисперсии загрязнений вокруг зданий - Ковалец, И.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The computational fluid mechanics model of is atmospheric
dispersion in the vicinity of buildings is developed. The validation of model against
field experiment was performed. The application of model to problem of estimation of
concentration near contaminated buildings located at the territory of Pridneprovsky
Chemical Plant is presented.